Ecologia reprodutiva do peixe-donzela, Stegastes fuscus cuvier, 1830 (osteichthyes: pomacentridae) em arrecifes rochosos da praia de Búzios, Rio Grande do Norte, Brasil - Souza, Liliane de Lima Gurgel (2006)
The reproductive ecology of fish plays a key role both for rational exploitation methods and for protective measures of natural stocks. The purpose of this study was to analyze the reproductive aspects of the damsel-fish, Stegastes fuscus, during October 2004 to September 2005, in the coastal rocky reefs of Búzios Beach, Nísia Floresta, RN. Fish were captured using hooks and hand nets, during low tide. Reproduction was determined using sexual ratio, mean length of first maturation (L50), absolute fecundity and macroscopic characteristics of gonads. The following parameters were related to gonadosomatic index (GSI): condition factor (CF), hepatosomatic index (HSI), rain fall and temperature. In relation to sex distribution, it was observed that 78% were females and 22% were males. The L50 was 6.2 cm for females and 7.0 for males. Average fecundity was 6832 oocytes. Results showed that S. fuscus had better body condition in the months prior to spawning, particularly during initial and intermediate stages of maturation. Five stages of gonadal maturation were identified through macroscopic analysis: immature, in maturation, mature, spent and resting. The HSI was inversely related to the GSI. This was possibly due to the reproductive cycle of this species which was associated to the dry period of this region. During this period, low rain fall and high temperatures provide an propitious reproductive condition for the study species